2009
DOI: 10.1002/pi.2712
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun poly(L‐lactic acid)/hydroxyapatite composite fibrous scaffolds for bone tissue engineering

Abstract: Poly(L‐lactic acid) (PLLA) is one of the most studied synthetic biodegradable polymeric materials as a bone graft substitute. Taking into account the osteoconductive property of hydroxyapatite (HAp), we prepared fibrous matrices of PLLA without and with HAp particles in amounts of 0.25 or 0.50% (w/v, based on the volume of the base 15% w/v PLLA solution in 70:30 v/v dichloromethane/tetrahydrofuran). These fibrous matrices were assessed for their potential as substrates for bone cell culture. The presence of HA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
8

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 36 publications
1
20
0
8
Order By: Relevance
“…This finding is highly consistent with those of Sui et al [7] who reported that the cell adhesion and growth on electrospun PLA/HA hybrid membranes were far better than on pure PLA membranes. Similar results were also found by Chuenjitkuntaworn et al [40]. Additionally, Li et al [41] reported a decrease in vinculin expression on neat PLA surfaces in comparison to gelatin-modified PLA surfaces when human umbilical vein endothelial cells (HUVEC) were used.…”
Section: Discussionsupporting
confidence: 71%
“…This finding is highly consistent with those of Sui et al [7] who reported that the cell adhesion and growth on electrospun PLA/HA hybrid membranes were far better than on pure PLA membranes. Similar results were also found by Chuenjitkuntaworn et al [40]. Additionally, Li et al [41] reported a decrease in vinculin expression on neat PLA surfaces in comparison to gelatin-modified PLA surfaces when human umbilical vein endothelial cells (HUVEC) were used.…”
Section: Discussionsupporting
confidence: 71%
“…The presence of HA particles at 0.50% w/v concentration not only promoted the attachment and the proliferation of mouse pre-osteoblastic cells (MC3T3-E1) but also increased the expression of osteocalcin mRNA, and the extent of mineralization after the cells had been cultured on the scaffolds for 14 and 21 days, respectively [71].…”
Section: Hybrid Scaffolds With Synthetic Polymersmentioning
confidence: 99%
“…In another approach, blends of synthetic polymers (e.g. PCL, PLLA) with natural polymers such as HA have been investigated. Scaffolds consisting of three different constituents have also been reported, for example PCL/collagen/HA, PLLA/collagen/HA, gelatin/HA/PLCL and PCL/PLGA/HA .…”
Section: Adjusting Mechanical Performance For Bone and Vascular Tissumentioning
confidence: 99%